Policy and Practice: Claiming Space for Labour Rights within the United Kingdom Modern Slavery Crusade - Robinson, Caroline (Anti-Trafficking Review, 2015)
The focus of this article is on advocacy opportunities provided by the anti-trafficking framework in a new political climate. Through the case study of the United Kingdom (UK) Modern Slavery Act 2015 deliberations the article explores opportunities to use political interest in human trafficking to advocate labour rights and protections for vulnerable workers. The article explores how, largely cynical, political motivations for the debate on ‘modern slavery’ in the UK, provided an opportunity to reframe the anti-trafficking discourse in this context. Whilst migration control and labour market deregulation are key priorities for the UK government, the Modern Slavery Act process enabled advocates to highlight the impact of such measures on vulnerable, predominantly migrant, workers. It also ultimately served to persuade decision makers to make a connection between widespread labour abuses and severe labour exploitation. Through this case study the article argues for engagement with anti-trafficking frameworks to both highlight and harness the political rhetoric, and maximise the space provided for promoting the rights of vulnerable workers.